The Influence of Content and Source on Tourists’ Decisions to Visit Kajoetangan Heritage Village - Revvalina Vania Putri Setiyawan; Sheidy Yudhiasta (International Journal of Business and Quality Research, 2026)
This study intends to examine the influence of the dimensions of Electronic Word of Mouth (E-WOM) namely, Source and Content on tourists’ decisions to visit Kampung Heritage Kajoetangan in Malang. This study used an explanatory research design and a quantitative approach. Data were obtained using a questionnaire provided to travelers who had previously visited Kajoetangan Heritage Village in Malang using purposive sampling, and were subsequently analyzed using multiple linear regression analysis with IBM SPSS Statistics 29. The results reveal that, concurrently, the factors Source and Content have a considerable effect on tourists’ visit decisions. Partially, the “Source” variable has a favorable and substantial effect on the decision to visit, while the “Content” variable does not have a meaningful effect. It is anticipated that this study will help the management of Kampung Heritage Kajoetangan Malang improve the effectiveness of information dissemination through digital media, especially by strengthening the credibility of information sources to encourage tourists' visitation decisions. These findings show that the credibility of the information source plays a more dominant role in influencing tourists' decisions to visit than the quality of the information content.